PENGARUH KEMAMPUAN DAN KEAHLIAN TERHADAP KINERJA PEGAWAI DI KANTOR DESA SEKECAMATAN KULO - Nurhikma; Adnan, Andi Astinah; Erfina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to examine whether ability and expertise have an influence on employee performance at the Village Office in Kulo Sub-district. This study uses a quantitative approach with a population of 57 people. The sample was taken saturated, and the data collection technique used was a questionnaire. Data analysis was carried out using simple linear regression and multiple linear regression with the help of SPSS version 22.0 for Wondows. Based on the results of the simple linear regression test, the significance value of X1 is 0.000 <0.05, indicating that ability has an influence on employee performance at the Village Office in Kulo Sub-district. Likewise, the significance value of X2 is 0.000 <0.05, indicating that performance has an influence on employee performance at the Kulo District Village Office. Based on the results of multiple linear regression tests, it shows that the significance value of X1 is 0.000 <0.05, indicating that ability has a partial influence on employee performance, as well as the significance value of X2 of 0.021 <0.05, indicating that expertise has a partial influence on employee performance. So it can be concluded that ability and expertise affect employee performance at the Village Office in Kulo Sub-district.